PENERAPAN MODEL ROLE PLAYING DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS PADA SISWA KELAS V SDN 1 BRECONG TAHUN AJARAN 2015/2016 - nafisah, lulu (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract. The Application of Role Playing Model with Audio Visual Media to Increase Motivation and Learning Outcomes of Social Studies V Grade SDN 1 Brecong Academic Year 2015/2016. The purpose of this study is to improve motivation and learning outcomes of social studies, and describe the problems and solutions implementation of the role playing model with audio-visual media. This research is collaborative-classroom action reseach in three cycles and each cycle consist of planning, implementation, observation, and reflection. The subjects were students of fifth grade SDN 1 Brecong. The results showed that the application of role playing model with audio-visual media can improve motivation and learning outcomes social studies. Problem in the application of the role playing model with audio-visual media, namely in setting teacher pay less attention to players according to ability, students are less animating role, less active students ask when learning activities. As for the solution of the problems that teachers pay more attention to the ability of the students in setting the player, more students animating role with the guidance of teachers, and students are more active in asking. Keywords: role playing, audio-visual, learning outcomes, social studies Abstrak. Penerapan Model Role Playing dengan Media Audio Visual untuk Meningkatkan Motivasi dan Hasil Belajar IPS pada Siswa Kelas V SDN 1 Brecong Tahun Ajaran 2015/2016. Tujuan penelitian ini adalah untuk meningkatkan motivasi dan hasil belajar IPS serta mendeskripsikan kendala dan solusi penerapan model role playing dengan media audio visual. Penelitian tindakan kelas ini merupakan penelitian kolaboratif yang dilaksanakan dalam tiga siklus dengan tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN 1 Brecong. Hasil penelitian menunjukkan penerapan model role playing dengan media audio visual dapat meningkatkan motivasi dan hasil belajar IPS. Kendala yang muncul dalam penerapan model role playing dengan media audio visual,yaitu dalam menetapkan pemain guru kurang memperhatikan sesuai kemampuan siswa, siswa kurang menjiwai perannya, siswa kurang aktif bertanya saat kegiatan pembelajaran. Adapun solusi dari kendala tersebut yaitu guru lebih memperhatikan kemampuan yang dimiliki siswa dalam menetapkan pemain, siswa lebih menjiwai perannya dengan dibimbing guru, dan siswa lebih aktif bertanya. Kata kunci: role playing, audio visual, hasil belajar, IPS